Responsibility of Notary/PPAT Regarding The Issuance of Sale and Purchase Deeds Based on Power of Attorney to Sell Without the Knowledge of the Legitimate Owner (Analysis of Decision Number 29/PDT.G/2025/PN.MTR) - Ni Putu Novia Apriyanti Ardani; Djumardin Djumardin; Diman Ade Mulada (NOTARIIL Jurnal Kenotariatan, 2026)
The objectives of this study are to examine the validity of sale and purchase deeds issued by a Notary/PPAT based on a power of attorney to sell executed without the knowledge of the rightful owner according to the laws and regulations in Indonesia, the considerations of judges in making decisions related to the responsibility of a Notary/PPAT for issuing sale and purchase deeds based on the abuse of a power of attorney to sell, and the responsibility of a Notary/PPAT in providing legal protection to the rightful owner as a result of the transfer of ownership of land based on a legally defective sale and purchase deed. The type of research used is normative legal research. The research approaches used are the Statutory Approach, Case Approach, and Conceptual Approach. Legal materials are collected through library research. The analytical method used by the author is qualitative. Based on the discussion results, first, the AJB created due to the abuse of power to sell for guaranteeing debt repayment violates the validity requirements of an agreement under Article 1320 of the Civil Code and the UUHT, and is classified as an unlawful act. Therefore, the transfer of land rights without the consent of the legitimate owner has no legal force and can be annulled through a court decision. Second, the considerations of the Panel of Judges in the decision regarding the sale conducted by the Defendants over the object of dispute based on the power of attorney to sell without the plaintiff's knowledge do not meet the requirements of a valid agreement and result in losses for the plaintiff. Article 1820 of the Civil Code emphasizes that the recipient of the power of attorney is obliged to provide a report regarding all processes of executing their power. Thus, the legal act is declared invalid and annulled. Third, the accountability of a Notary/PPAT for a deed that is legally defective due to proven errors in the exercise of authority and official duties can be held accountable administratively, civilly, or criminally according to the type of violation.